Anticipatory 50-kHz Precontact Ultrasonic Vocalizations and Sexual Motivation: Characteristic Pattern of Ultrasound Subtypes in an Individual Analyzed Profile - Bogacki-Rychlik, Wiktor; Rolf, Mateusz; Bialy, Michal (Frontiers in Behavioral Neuroscience, 2021)
We verified the hypothesis of the existence of forms of individual-specific differences in the emission of anticipatory precontact vocalization (PVs) indicating individualization related to sexual experience and motivation in male rats. Long-Evans males were individually placed in a chamber and 50-kHz ultrasounds were recorded during five-minute periods. In experiment 1, PVs were recorded before the introduction of a female in four consecutive sessions during the acquisition of sexual experience. In experiment 2, PVs were analyzed in three groups of sexually experienced males: with the highest, moderate, and the lowest sexual motivation based on previous copulatory activity. In both experiments, the total number of ultrasounds, as well as 14 different specific subtypes, was measured. The ultrasound profiles for each male were created by analyzing the proportions of specific dominant subtypes of so-called 50-kHz calls. We decided that the dominant ultrasounds were those that represented more than 10% of the total recorded signals in a particular session. The number of PVs was positively correlated with the acquisition of sexual experience and previous copulatory efficiency (measured as the number of sessions with ejaculation). Furthermore, PVs showed domination of the frequency-modulated signals (complex and composite) as well as flat and short with upward ramp ultrasounds with some individual differences, regardless of the level of sexual motivation. The results show a characteristic pattern of PVs and confirm the hypothesis that the number of PVs is a parameter reflecting the level of sexual motivation.